1999
DOI: 10.1007/s007870050132
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in the ratings of behaviors of communicatively impaired autistic and non-autistic preschool children

Abstract: Typically, children with disabilities are evaluated clinically by a number of professionals with different backgrounds whose task is to provide a diagnosis and an intervention plan. This study was carried out to describe interrater agreement for pairs of independent observers rating with different instruments the behaviors of 505 communicatively impaired autistic and nonautistic preschool children. Observers were parents, teachers, neurologists, and psychiatrists. Parents and teachers responded to behavioral q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
4
8
1
Order By: Relevance
“…Our results are consistent with prior investigations which have shown that agreement is usually higher when the disorder is more severely impairing (Pearson et al, 2012; Rapin et al 1999). Parent-teacher agreement may be higher for more severely affected children because these children have more obvious maladaptive behaviors that they exhibit at home and at school.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with prior investigations which have shown that agreement is usually higher when the disorder is more severely impairing (Pearson et al, 2012; Rapin et al 1999). Parent-teacher agreement may be higher for more severely affected children because these children have more obvious maladaptive behaviors that they exhibit at home and at school.…”
Section: Discussionsupporting
confidence: 93%
“…Clinicians also may consider using multiple methods of assessment, reflecting both the structure of the classroom and the flexibility of the home environment. Improving the efficiency of multi-informant assessment and home-school collaboration is necessary to provide a more comprehensive, reliable depiction of social functioning that may ultimately determine the nature, cost, and intensity of interventions, and perhaps more importantly, improve outcomes for children with autism (Jepsen et al, 2012; Murray et al, 2009; Rapin et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations